133k views
5 votes
Please help me out with this

Please help me out with this-example-1

1 Answer

4 votes

Answer:

A) 4x - 2y + 3z = - 3

B) 2x - 3y + 2z = 1

C) 6x + 10z = -2

Multiply A) by -1.5

A) -6x +3y -4.5z = 4.5 Then adding to B)

B) 2x - 3y + 2z = 1

D) -4x -2.5z = 5.5 then we add this to C)

C) 6x + 10z = -2 Now we multiply D) by 1.5

D) -6x -3.75z = 8.25 Adding C) + D)

6.25z = 6.25

z = 1 Then putting z = 1 into A) and B)

A) 4x - 2y + 3 = - 3 equals A) 4x -2y = -6

B) 2x - 3y + 2 = 1 equals B) 2x -3y = -1 we divide A) by -2

A) -2x + y = 3 then adding to B

B) 2x - 3y = -1

-2y = 2

y = -1

FINALLY solving for x we'll use equation A)

A) 4x - 2*-1 + 3*1 = - 3

A) 4x +2 + 3 = -3

A) 4x = -8

x = -2

(Yes, it's just that easy. LOL)

Explanation:

User Nad Pat
by
6.3k points